Rewriting Viral Fate: Epigenetic and Transcriptional Dynamics in KSHV Infection - Chunyan Han; Danping Niu; Ke Lan (Viruses)
Kaposi’s sarcoma-associated herpesvirus (KSHV), a γ-herpesvirus, is predominantly associated with Kaposi’s sarcoma (KS) as well as two lymphoproliferative disorders: primary effusion lymphoma (PEL) and multicentric Castleman disease (MCD). Like other herpesviruses, KSHV employs two distinct life cycles: latency and lytic replication. To establish a lifelong persistent infection, KSHV has evolved various strategies to manipulate the epigenetic machinery of the host. In latently infected cells, most viral genes are epigenetically silenced by components of cellular chromatin, DNA methylation and histone post-translational modifications. However, some specific latent genes are preserved and actively expressed to maintain the virus’s latent state within the host cell. Latency is not a dead end, but the virus has the ability to reactivate. This reactivation is a complex process that involves the removal of repressive chromatin modifications and increased accessibility for both viral and cellular factors, allowing the activation of the full transcriptional program necessary for the subsequent lytic replication. This review will introduce the roles of epigenetic modifications in KSHV latent and lytic life cycles, including DNA methylation, histone methylation and acetylation modifications, chromatin remodeling, genome conformation, and non-coding RNA expression. Additionally, we will also review the transcriptional regulation of viral genes and host factors in KSHV infection. This review aims to enhance our understanding of the molecular mechanisms of epigenetic modifications and transcriptional regulation in the KSHV life cycle, providing insights for future research.